The Quest for a Realistic Four-dimensional Cosmology - Neupane, Ishwaree P (Himalayan Physics, 2011)
The existence of a small and positive cosmological constant attributed to gravitational vacuum energy (or dark energy) in the present-day universe appears to be the most pressing obstacle as well as opportunity to significantly improving the models of four-dimensional cosmology from fundamental theories of gravity, including string theory and modern Kaluza-Klein theories. In seeking to resolve this problem, one naturally wonders if the real world can somehow be interpreted as an inflating de Sitter "brane" embedded in a five or even higher-dimensional space-time described by warped or non-factorizable geometry. In this scenario, the four-dimensional cosmological constant may well be determined in terms of two length scales: one is a scale associated with the size of extra dimensions and the other is a scale associated with the expansion rate of the universe, which is also related to the warping of extra spaces. Key words: Cosmology The Himalayan Physics Vol.1, No.1, May, 2010 Page: 18-24 Uploaded Date: 28 July, 2011